(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The article presents the opinions and views of foreign scientists on the types, content, relevance, didactic elements and models of conceptual teaching in the center of pedagogical skills. It is especially revealed from a scientific point of view that the contextual teaching model is an integral part of the modern pedagogical process and is a tool that ensures that education is practice-oriented.